VD_FINDINFO AI 78/12 - 201/2012 vom 12. Juni 2012 - VD Tribunal cantonal (2012)
RADIATION DU RÔLE, MOTIVATION DE LA DEMANDE, DÉLAI FIXÉ PAR LE JUGE | 61 let. b LPGA, 25 LPA-VD, 27 al. 4 LPA-VD, 27 al. 5 LPA-VD, 79 LPA-VD, 94 LPA-VD